The international marketing environment: textbook content versus educators' views - Leonidou, Leonidas C.; Kaminarides, John S.; Panayides, Photis (My University, 2007)
The article analyzes the content of 18 international marketing academic textbooks with regard to factors comprising the global marketing environment. Three broad categories of factors are identified, the macro (i.e., physical, demographic, and socio-cultural), meso (i.e., economic, political-legal, and technological), andmicro (i.e., intermediaries, competitors, market, and customers). In each of the subcategories, 10 different factors affecting global marketing were extracted. By measuring the extent of coverage given to each factor in each textbook, the relative emphasis placed collectively was established. These results were subsequently compared and contrasted to the views of 71 academics teaching international marketing; revealing the existence of gaps between the importance attached to most of the elements comprising the international marketing environment, and the coverage provided in academic textbooks
Keywords: International business; Marketing; Teaching